HIV-1 Gag Non-Cleavage Site PI Resistance Mutations Stabilize Protease/Gag Substrate Complexes In Silico via a Substrate-Clamp - Gary S. Laco (MDPI AG, 2021)
HIV-1 protease active site inhibitors are a key part of antiretroviral therapy, though resistance can evolve rendering therapy ineffective. Protease inhibitor resistance typically starts with primary mutations around the active site, which reduces inhibitor binding, protease affinity for substrate cleavage site residues P4-P4', and viral replication. This is often followed by secondary mutations in the protease substrate-grooves which restore viral replication by increasing protease affinity for cleavage site residues P12-P5/P5'-P12', while maintaining resistance. However, mutations in Gag alone can also result in resistance. The Gag resistance mutations can occur in cleavage sites (P12-P12') to increase PR binding, as well as at non-cleavage sites. Here we show in silico that Gag non-cleavage site protease inhibitor resistance mutations can stabilize protease binding to Gag cleavage sites which contain structured subdomains on both sides: SP1/NC, SP2/p6, and MA/CA. The Gag non-cleavage site resistance mutations coordinated a network of H-bond interactions between the adjacent structured subdomains of the Gag substrates to form a substrate-clamp around the protease bound to cleavage site residues P12-P12'. The substrate-clamp likely slows protease disassociation from the substrate, restoring the cleavage rate in the presence of the inhibitor. Native Gag substrates can also form somewhat weaker substrate-clamps. This explains the 350-fold slower cleavage rate for the Gag CA/SP1 cleavage site in that the CA-SP1 substrate lacks structured subdomains on both sides of the cleavage site, and so cannot form a substrate-clamp around the PR.